2015
DOI: 10.1038/srep18558
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Recombinant Enterovirus Type EV-A89 with Low Epidemic Strength in Xinjiang, China

Abstract: Enterovirus A89 (EV-A89) is a novel member of the EV-A species. To date, only one full-length genome sequence (the prototype strain) has been published. Here, we report the molecular identification and genomic characterization of a Chinese EV-A89 strain, KSYPH-TRMH22F/XJ/CHN/2011, isolated in 2011 from a contact of an acute flaccid paralysis (AFP) patient during AFP case surveillance in Xinjiang China. This was the first report of EV-A89 in China. The VP1 coding sequence of this strain demonstrated 93.2% nucle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
21
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 51 publications
2
21
0
Order By: Relevance
“…The circulation of EV-C strains should be carefully monitored, because several outbreaks of poliomyelitis caused by cVDPVs containing sequences in the non-structural protein coding region from unidentified sources that are considered to be a result of recombination with EV-C have been documented 21 22 24 . Moreover, many recent studies have shown that such enterovirus species exist as a worldwide reservoir of genetic material, comprising a limited quantity of coding region sets defining a finite number of serotypes and a range of non-structural genes that recombine frequently to produce new virus variants 28 36 40 41 . Recombination between a slightly pathogenic vaccine poliovirus mutant and an EV-C strain may result in a recombinant that is more pathogenic, replicates to higher titers, and is maintained in circulation 23 36 42 .…”
Section: Discussionmentioning
confidence: 99%
“…The circulation of EV-C strains should be carefully monitored, because several outbreaks of poliomyelitis caused by cVDPVs containing sequences in the non-structural protein coding region from unidentified sources that are considered to be a result of recombination with EV-C have been documented 21 22 24 . Moreover, many recent studies have shown that such enterovirus species exist as a worldwide reservoir of genetic material, comprising a limited quantity of coding region sets defining a finite number of serotypes and a range of non-structural genes that recombine frequently to produce new virus variants 28 36 40 41 . Recombination between a slightly pathogenic vaccine poliovirus mutant and an EV-C strain may result in a recombinant that is more pathogenic, replicates to higher titers, and is maintained in circulation 23 36 42 .…”
Section: Discussionmentioning
confidence: 99%
“…Molecular serotyping methods based on sequence variation in the VP1 region correlate with the classification based on antigenic properties 21 26 , and have recently replaced the neutralization test as the gold standard for enterovirus serotyping. Since the invention and application of molecular serotyping methods, a considerable number of new EV serotypes have been identified in many Chinese provinces, especially in Shandong 13 27 , Yunnan 14 , Xinjiang 28 29 , Tibet 3 15 30 , and Guangdong 31 . In this study, we report the full-length genome sequence of a recently identified novel serotype, EV-B84, which was also obtained from AFP case surveillance.…”
Section: Discussionmentioning
confidence: 99%
“…The emergence of molecular typing technology has greatly changed the current situation and accelerated the discovery of novel enteroviruses, which have been increasingly reported 9,[22][23][24] . Currently, there are only two EV-B83 full-length genomic sequences and twelve in the VP1 region with lengths over 600 bp available in GenBank.…”
Section: Discussionmentioning
confidence: 99%